2015
DOI: 10.21767/2254-6081.100042
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Property of Gotu kola (Centella asiatica) from the Selection of Traditional Applications to the Novel Phytotherapy

Abstract: Background: This comprehensive research article analyzes the remedial and memory enhancing capacities of Centella asiatica (L.) Urban [Apiaceae], also known as C. asiatica or Indian pennywort. C. asiatica has been used for decades in parts of South-east Asia and India as an alternative herbal remedy for skin conditions, wound healing and memory improvement. The central focus of this research article was aimed to determine the positive influence of C. asiatica (dried form, whole plant, or aqueous extract) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Animal studies have revealed that C. asiatica improves memory, increases response time, and aids in wound healing. C. asiatica aqueous extract in dose-dependent amounts decreased the appearance of aging skin, collagen, and topical scars[ 81 ]. In vivo and in vitro studies of the methanolic fraction of C. asiatica exhibited great polyvalent activity, indicating that it has the potential to be an efficient wound healer[ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have revealed that C. asiatica improves memory, increases response time, and aids in wound healing. C. asiatica aqueous extract in dose-dependent amounts decreased the appearance of aging skin, collagen, and topical scars[ 81 ]. In vivo and in vitro studies of the methanolic fraction of C. asiatica exhibited great polyvalent activity, indicating that it has the potential to be an efficient wound healer[ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also reversed aging induced amnesia due to natural aging of mice suggesting that the compound in this plant may prove to be useful in restoring memory in older individuals as well as in patients with age-associated dementia 11. Centella asiatica: [40][41][42][43][44][45][46][47][48] It Water extract of this plant has shown mitigation of Aβinduced cell death and also it has attenuated Aβ-induced alternations in Tau expression and phosphorylation in cell lines (according to Gray nora. et.al,).…”
Section: Nardostachys Jatamanasi (Jatamansi): 10mentioning
confidence: 99%
“…While, Orhan [7] reported that Asiatic pennywort could be suggested to be a desired phytopharmaceutical with neuroprotective effect. According with, Hamidpour et al [8] were found that Asiatic pennywort enhanced memory and cognitive effect.…”
Section: Introductionmentioning
confidence: 99%